Critical Evaluation of the Impact of Disturbance Dynamo on Equatorial Ionosphere During Daytime. Issue 11 (21st November 2018) - Pandey, Kuldeep; Chakrabarty, D.; Sekar, R.
Abstract: Based on careful analysis of 16 years of hourly variations of the strength of equatorial electrojet (EEJ) derived using the ground‐based magnetometers over the Indian sector, the role played by disturbance dynamo electric field disturbances on equatorial ionosphere is identified. It is found that most prominent cases of the effects of disturbance dynamo occurred during equinoctial months in high solar activity period. In three extreme cases, the reduction in EEJ strength from quiet time average values of the respective month is more than twice the standard deviations for at least 3 hr. Based on the methodology described in Pandey et al. (2017, https://doi.org/10.1016/j.jastp.2017.03.012 ), it is found that the westward electric field perturbations are as large as 0.7 ± 0.2 to 1.2 ± 0.3 mV/m around noon hours for these three cases. In contrast to the expectation of disturbance dynamo electric field perturbations over equatorial latitudes from the earlier models, these values during daytime are significantly larger and even caused reversals of EEJ on two occasions. A possible additional source to augment the reduction in the electric field is indicated. Key Points: Large reduction in equatorial electrojet strength during daytime associated with disturbance dynamo Corresponding changes in electric field on some occasions are much larger than those reported earlier Additional influence of semidiurnal tides is proposed to account for the large reduction